PKM PENDAMPINGAN DAN PELATIHAN OLAHRAGA RENANG UNTUK ANAK USIA DINI - Gatot Jariono; Nur Subekti; Vera Septi Sistiasih; Muhad Fatoni; Eko Sudarmanto; Pungki Indarto; Nurhidayat Nurhidayat; Moch. Danny Yudha Pradana; Ahmad Sova Sundoro; Dwi Adiyana Bayu Kristiyadi; Dwi Endri Mei Minawati; Aulia Ajeng Destiana; Wulandari Wulandari; Rafli Muhammad; Ginting Baharudin Putra; Sae Digdaya Nyatara; Tunjung Marganingrum (Indonesian Collaboration Journal of Community Services, 2022)
Promoting swimming from the community, including young people, requires serious attention. Because swimming is not only talking about physical fitness development activities related to improving motor skills but also relating to strengthening national identity in this era of globalization. Without the intervention of the transformation of swimming, the Indonesian nation will be worse off because it is a nation that does not have a strong character. To strengthen the sport of swimming, efforts are made to collect data and standardize swimming from an early age to adulthood. Furthermore, it is necessary to socialize swimming sports through PkM activities. In this context, placing swimming as part of the curriculum for learning swimming in early childhood is an important thing to do. Through various ways in introducing the sport of swimming, it can become part of the life of the Indonesian nation itself and is ready to build the nation towards a nation that has character and has the identity of the Indonesian nation. The formation of early childhood character through swimming. In today's era, many children prefer advanced technology compared to actual sports, this will have an impact on social interaction and character in children. At the time of doing the introduction of swimming with an indirect play approach to instill the values ??of being sporty, honest, tenacious, and patient.                                                          PkM aims to 1) Provide Knowledge to partners related to basic swimming techniques in early childhood and the dominant physical component in swimming, 2) Provide partner knowledge in the utilization of science and technology and sports in swimming in early childhood, 3) Provide swimming guidebooks in early childhood so that partners can provide pursuit for the introduction of water in basic swimming techniques in early childhood.  Quality and productive, where so far the teachers only do teaching following experience and do not document the development of their learners. The method implemented in this activity is based on the results of discussions between the proposer and partners, Furthermore, the researcher concluded that the priority of the problem agreed to be resolved during the implementation of the PkM program is to provide education and training accompanied by practice to partners making basic swimming instruction modules in early childhood where the content in the guidance on the utilization of the development of sports science and technology is the basic technique of swimming in children.  Early age that will facilitate partners by utilizing guidebook products is considered the level of attractiveness, effectiveness, and efficiency of the swimming guidebook developed/modified by the Service team. PkM results can be concluded that swimming assistance and training for early childhood can increase the enthusiasm of students in participating in these activities, this is evidenced by students feeling happy through water games, safety in the water, moving skills through the approach of play